Tracheal intubation by paramedics under limited indication criteria may improve the short-term outcome of out-of-hospital cardiac arrests with noncardiac origin - Takei, Yutaka; Enami, Miki; Yachida, Takahiro; Ohta, Keisuke; Inaba, Hideo (Journal of anesthesia, 2010)
Purpose It is not clear whether advanced airway management (AAM) with an endotracheal tube (ET) by paramedics may improve the outcome of out-of-hospital cardiac arrest (OHCA) compared with the use of a bag-valve-mask device (BVMD) and other AAM devices. Methods We analyzed 2,586 adult cases of OHCA without administration of adrenaline, witnessed or recognized by citizens in subjects transported to hospital by paramedics between 1 July 2004 and 31 March 2008 in Ishikawa, Japan, to determine whether AAM with an ET used under limited indication criteria may improve the outcome of OHCA. Results The airway was managed with an ET in 263 cases, other AAM devices in 660 cases, and a BVMD in 1,539 cases. The AAM failed or was discontinued in 124 cases, which were excluded from the analysis. The incidence of sustained return of spontaneous circulation (ROSC) was significantly higher in cases of AAM with an ET (30%) than in AAM with other devices (20.2%) and in the standard procedure with a BVMD (21.3%). The AAM with an ET did not significantly affect 1-year survival. Multiple regression analysis indicated that tracheal intubation (odds ratio = 1.503, 95% confidence interval 1.081–2078), but not patient management by paramedics qualified for ET use, was an independent factor associated with sustained ROSC. Conclusion When subjects with difficult airway are excluded, tracheal intubation according to the limited indication criteria and well-organized protocol in Japan may improve the short-term outcome of OHCA of noncardiac origin. A large prospective study is needed to determine the general effects of tracheal intubation on the long-term outcome of OHCA with disturbed ventilation.